Integrating ethical considerations into digital business strategy: a mini systematic literature review - Astadi Pangarso; Heru Nugroho; Wardani Muhamad; Robbi Hendriyanto; Ade Gafar Abdullah (Journal of Innovation in Business and Economics, 2026)
The principle of "leaving no one behind" is increasingly central to the sustainability of digital business. Because digital business strategies directly affect a wide spectrum of stakeholders, embedding ethics into strategy formulation is essential for responsible and sustainable value creation. The rapid advancement of digital technologies, however, continues to generate complex ethical tensions across stakeholder interests. A digital business strategy that explicitly integrates ethical principles is more likely to be successfully implemented and to produce sustainable outcomes. To the best of the authors' knowledge, scholarly work that explicitly links ethics with digital business strategy remains limited. This study therefore aims to provide scientific evidence that ethics is an indispensable component of digital business strategy formulation. The analysis and synthesis of secondary data follow a systematic literature review (SLR) approach, supported by bibliometric analysis of publications indexed in the Scopus database, Litmaps, and complemented by a Scopus AI concept map. The findings contribute to the literature on business ethics and strategic management, and offer an evidence-based rationale for practitioners to integrate ethical considerations into their digital business strategies.